1993
DOI: 10.1021/bi00086a022
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of P-glycoprotein transport by protein kinase inhibition

Abstract: Previous studies of P-glycoprotein have demonstrated that its function can be modulated by phosphorylation. In the present study, inhibition of protein kinase C with calphostin C or stauroporine or prolonged treatment with the phorbol ester TPA decreased phosphorylation of P-glycoprotein, and impaired transport of vinblastine. Calphostin C also inhibited transport of actinomycin D, vincristine, rhodamine, and azidopine in SW620 Ad300 multidrug-resistant human colon carcinoma cells. Photoaffinity labeling of P-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 33 publications
5
49
0
1
Order By: Relevance
“…PKC activators also increased drug accumulation and decreased drug sensitivity in MCF-7/Adr (Fine et al, 1988) and KM12L4a cells (Dong et al, 1991), and induced MDRJ gene expression in normal human lymphocytes (Chaudhary and Roninson, 1992). Conversely, a variety of PKC inhibitors, such as staurosporine (Sato et al, 1990), the staurosporine analogues CGP 41251 (Utz et al, 1994; Budworth et al, 1996) and GF 109203X , calphostin C (Bates et al, 1993) and safingol (Sachs et al, 1995), reversed P-gp-mediated mdr. However, reversal of drug resistance caused by staurosporine analogues is probably associated with direct interaction with P-gp rather than with PKC inhibition (Smith and Zilfou, 1995;Gekeler et al, 1996;Goodfellow et al, 1996;Budworth et al, 1996).…”
mentioning
confidence: 99%
“…PKC activators also increased drug accumulation and decreased drug sensitivity in MCF-7/Adr (Fine et al, 1988) and KM12L4a cells (Dong et al, 1991), and induced MDRJ gene expression in normal human lymphocytes (Chaudhary and Roninson, 1992). Conversely, a variety of PKC inhibitors, such as staurosporine (Sato et al, 1990), the staurosporine analogues CGP 41251 (Utz et al, 1994; Budworth et al, 1996) and GF 109203X , calphostin C (Bates et al, 1993) and safingol (Sachs et al, 1995), reversed P-gp-mediated mdr. However, reversal of drug resistance caused by staurosporine analogues is probably associated with direct interaction with P-gp rather than with PKC inhibition (Smith and Zilfou, 1995;Gekeler et al, 1996;Goodfellow et al, 1996;Budworth et al, 1996).…”
mentioning
confidence: 99%
“…Se ha demostrado que la exposición de células con fenotipo MDR a activadores de PKC aumenta la fosforilación de la Pgp, disminuye la acumulación del medicamento e incrementa la resistencia a los fármacos (101,102); al contrario, la presencia de inhibidores de PKC disminuye la fosforilación e incrementa la acumulación del medicamento (103).…”
Section: Posibles Estrategias Para Revertir El Fenotipo Mdrunclassified
“…A popular and widely used compound is the protein kinase C activator TPA, first reported by Hamada et al (1987) to stimulate P-glycoprotein phosphorylation, and first reported by Fine et al (1988) to influence MDR drug accumulation. Short-term TPA treatment stimulates P-glycoprotein phosphorylation and reduces drug accumulation in a wide variety of MDR cell lines (Aftab et al, 1994;Bates et al, 1992;Bates et al, 1993;Chambers et al, 1990;Chambers et al, 1992;Yu et al, 1991). The effect of TPA on drug accumulation is dose-dependent, with a half-maximal effect at around 20 nM TPA, and is observed in MDR cells and not in the respective drug-sensitive cell line (Aftab et al, 1994;Chambers et al, 1992).…”
Section: Phosphorylation Of P-glycoproteinmentioning
confidence: 99%
“…Increased drug accumulation occurs in MDR cell lines treated with staurosporine or calphostin C, both effective inhibitors of P-glycoprotein phosphorylation (Aftab et al, 1994;Bates et al, 1993;Chambers et al, 1992;Ma et al, 1991). Sodium butyrate has also been shown to inhibit P-glycoprotein phosphorylation and cause an increase in accumulation of several cytotoxic drugs that are substrate for P-glycoprotein (Bates et al, 1992).…”
Section: Phosphorylation Of P-glycoproteinmentioning
confidence: 99%